Assessment of Antiretroviral Treatment Adherence among Children Attending Care at a Tertiary Hospital in Southeastern Nigeria. (5th February 2017) - Akahara, Cletus; Nwolisa, Emeka; Odinaka, Kelechi; Okolo, Seline
Abstract : Background . Adherence is the strongest predictor of successful treatment outcome among children infected with HIV. Our aim was to assess the antiretroviral drugs adherence status of HIV-infected children attending care at a tertiary hospital in Southeastern Nigeria. Method . The study involved a cross-sectional survey of 210 HIV-infected children attending care at a tertiary hospital in Southeastern Nigeria using self-report method of assessment. Optimal ART adherence is defined as patient taking not missing more than 1 dose of combined antiretroviral therapy medication in the preceding 2 weeks prior to the study. Result . A majority of the subjects 191 (91%) had good adherence. There was a significant relationship between adherence and patient educational level (p = 0.004 ), duration of treatment (p = 0.001 ), drug administrator (p = 0.005 ), and orphan status (p = 0.001 ). The motivating factor for adherence was "not falling sick as before" while stigma was the most discouraging factor. Conclusion . The adherence level in this study was good. Stigma was an important reason given by patient/caregivers for nonadherence. There is need for concerted effort in addressing this barrier to improve adherence and prevent the emergence of drug resistance and treatment failure.